Assessment of hand hygiene practices among nurses at a regional hospital in Kandahar, Afghanistan: A cross-sectional study based on the World Health Organization (WHO) ‘Your 5 Moments for Hand Hygiene’ guidelines - Abdul Qadeer Baseer; Asmatullah Usmani; Shafiqullah Mushfiq; Mohammad Hassan Hassand; Bilal Ahmad Rahimi; Abdul Wahid Monib; Mohammad Salim Daqiq; Parwiz Niazi (Belitung Nursing Journal)
Background: Hand hygiene is a critical component of infection prevention and control (IPC) in healthcare settings, as emphasized by the World Health Organization (WHO). However, compliance with recommended hand hygiene practices remains suboptimal in many resource-limited settings, including Afghanistan. Despite its importance, limited research has been conducted on hand hygiene practices in Afghan healthcare facilities, highlighting the need for further investigation.